Critical observations that shaped our understanding of the function(s) of intracellular glycosylation (O‐GlcNAc). Issue 23 (24th November 2018) - Zachara, Natasha E.
Abstract : Almost 100 years after the first descriptions of proteins conjugated to carbohydrates (mucins), several studies suggested that glycoproteins were not restricted to the serum, extracellular matrix, cell surface, or endomembrane system. In the 1980s, key data emerged demonstrating that intracellular proteins were modified by monosaccharides of O ‐linked β‐ N ‐acetylglucosamine (O‐GlcNAc). Subsequently, this modification was identified on thousands of proteins that regulate cellular processes as diverse as protein aggregation, localization, post‐translational modifications, activity, and interactions. In this Review, we will highlight critical discoveries that shaped our understanding of the molecular events underpinning the impact of O‐GlcNAc on protein function, the role that O‐GlcNAc plays in maintaining cellular homeostasis, and our understanding of the mechanisms that regulate O‐GlcNAc‐cycling. Abstract :